A whole‐systems approach for assessing measures to improve arable ecosystem sustainability. Issue 12 (21st December 2016) - Hawes, C.; Begg, G. S.; Iannetta, P. P. M.; Karley, A. J.; Squire, G. R.
Abstract: There is increasing pressure on the agricultural industry to maintain or increase production of high‐quality food while maintaining long‐term environmental sustainability. UK and EU policies and practices have been developed and implemented in an attempt to improve the sustainability and efficiency of arable farming and satisfy these potentially conflicting requirements. However, to the authors' knowledge, there has been no attempt to quantify whether new interventions have the desired effect on improving sustainability at a whole‐systems level. Most studies focus on one, or a few, elements of a specific system and therefore fail to account for trade‐offs and conflicts between the many different interacting components. Here, we propose a whole‐systems approach based on a suite of indicators for a complete and holistic assessment of the efficacy of policies to improve economic, environmental, and ecological sustainability.